Extracellular microRNA-223-5p Levels in Plasma, Saliva, and Gingival Crevicular Fluid in Periodontal Disease as a Potential Diagnostic Marker − A Case-Control Analysis - Dhathri Priya Bandi; Uma Sudhakar; Harinath Parthasarathy; Snophia Rani Rajamani; Balasubramanian Krishnaswamy (Wolters Kluwer Medknow Publications, 2023)
Introduction: Periodontal disease is distinguished by an aberrant host response to oral pathogens, leading to soft and hard tooth-supporting tissue inflammation. MicroRNAs are minute, single-stranded, highly dynamic biomolecules that control gene expression and regulate protein synthesis and functioning. Periodontal pathogenesis is associated with microRNA dysregulation. Accordingly, the proposed study will evaluate the extracellular circulating microRNA-223-5p in the plasma, saliva, and gingival crevicular fluid (GCF) of patients with periodontal disease. Materials and Methods: The research population comprised of 50 healthy individuals and 50 periodontitis patients. The clinical parameters of each participant were documented. Under sterile conditions, blood, saliva, and GCF were collected and stored at −80 °C. MicroRNA was isolated using microRNA extraction kits in accordance with the manufacturer's instructions, and the expression pattern of mir-223-5p in body fluids was analyzed using real-time polymerase chain reaction. Results: Expression of circulating extracellular microRNA-223-5p is elevated (P = 0.05) in plasma, saliva, and GCF by a fold of 2.511, 8.072, and 10.46, respectively. The clinical parameters, clinical attachment loss, and probing pocket depth correlated significantly and positively with an increase in miR-223-5p expression (P = 0.05). According to a ROC analysis, MicroRNA-223-5p may be a viable biomarker for periodontal disease, with a diagnostic accuracy of 84.50%. Conclusion: In conclusion, extracellular microRNA-223-5p detected in plasma, saliva, and GCF can be a reliable biomarker for periodontal disease. GCF is a potential body fluid for the analysis of microRNA-223 in relation to periodontal disease considering its expression is significantly higher in comparison to that of plasma and saliva. Due to their exceptional stability in body fluids, extracellular microRNAs can be employed as periodontal disease detectors, forecasting variables of treatment, and for the tailored modalities of treatment.